Densitometric osteoporosis: epidemiological profile of a municipality in southwest Goiás (Research, Society and Development, 2022)
Objectives: To evaluate the prevalence of osteoporosis in elderly patients in Mineiros-GO and compare the data found with data from the world population, identifying differences or similarities. Methodology: Retrospective, descriptive and cross-sectional study. Data were collected through access to bone densitometry (BMD) exams performed between 2017-2021 at the imaging diagnostic center in Mineiros-GO, in patients aged ≥ 60 years. For data analysis, the Statistical Package for Social Science version 26.0 was used. Results: Of the 315 patients, 97.1% were women. The mean age was 71 years. Among the sites surveyed, the forearm was performed less frequently. Elderly patients had lower bone mass values. Correlating bone mass value and sex, there was a difference only in radius 33%, in which women have lower values. Furthermore, T-score values compatible with osteoporosis were more prevalent in patients aged ≥70 years. This analysis in relation to sex did not show a significant difference. Finally, it was observed that no male individual performed control BMD. In contrast, most women who repeated the exam did so within 2 years or less after the first exam. Conclusion: Osteoporosis is a prevalent disease in our country. Therefore, attention from health professionals is necessary, especially risk groups, such as age ≥70 years. Furthermore, differences related to sex need to be considered, such as the low rate of BMD performance in men and lower values of bone mass in radius in women.